Effects of foliar-sprayed of selenium on distribution and accumulation of selenium in subcellular components of rice leaves - SUN Jianping1, LU Jiani1,2, LI Xiaojun2*, XUE Chenyang2 (Guangxi Zhiwu)
Foliar selenium spraying is an effective agronomic fortification to increase the selenium content of crops. In order to explore the distribution, accumulation characteristics and influencing factors of selenium in rice leaf fractions, and to improve the utilization efficiency of foliar selenium application, we compared the effects of different selenium forms, concentrations, treatment time and different surfactant carriers on the distribution and accumulation of selenium in the subcellular fractions of rice leaves using the leaf in vitro culture technique. The results were as follows:(1)Selenium was mainly distributed in the cell wall of rice leaves, followed by chloroplast and mitochondrial fractions, with the least in the cytosol.(2)The uptake capacity of sodium selenite in leaves within a few hours of leaf application of selenium fertilizer was significantly higher than that of nano-selenium, selenomethionine and yeast selenium, by 1.25-fold, 1.32-fold and 5.43-fold, respectively, and the migration capacity was about 1.26-fold higher than that of the remaining three.(3)The optimal amount of selenium applied to each leaf was 0.008 mg, and at that time the selenium content in chloroplasts and mitochondria reached the maximum value.(4)Three to seven hour after leaf application of selenium was the critical time point for selenium uptake and translocation in leaves.(5)Meanwhile, compared with cyclodextrin and alkyl glycoside, the addition of rhamnolipid to exogenous selenium at a concentration of 30 mg·L-1 promoted selenium uptake in rice leaves, and the content of the absorbed content increased by 80%. The above results provide the theoretical referecence for the subsequent understanding of selenium transport mechanisms in leaves, and also provide the support for the optimization of selenium formulations, the establishment of scientific selenium application systems, and the reduction of selenium ecological and environmental risks in the future.